Displacement Study of Glass Filled Unsaturated Polyester Composite Plate Under Transverse Impact Force. Issue 1 (September 2020) - Jayakumar, N.; Sinthuja, S.
Abstract: A finite element analysis is offered for analyzing the response of glass fiber filled reinforced unsaturated polyester composite plate due to transverse drop weight impact. The analysis could be used to estimate the displacements of the composite plate during impact and the stress distribution throughout the plate thickness. A thin SHELL 163 ANSYS-LS DYNA explicit element has been used for modeling the composite plate and SOLID 168 ANSYS-LS DYNA explicit element has been used for modeling the drop weight impactor.